(untitled) - Christopherson, Robert W. (Harlow, England, 2015)
For Introductory Physical Geography Courses Among the most highly regarded in physical geography, Robert Christopherson's bestselling texts are known for their meticulous attention to detail, currency, accuracy, and rich integration of climate change science. Geosystems: An Introduction to Physical Geography, Ninth Edition is uniquely organized to present Earth systems topics as they naturally occur: atmosphere, hydrosphere, lithosphere and biosphere. This interconnected and organic systems-based approach is highlighted in the strong pedagogical tools, structured learning path, and up-to-date information found in the text. This new edition presents bold new features that cultivate an active learning environment both in and outside the classroom
Keywords: Địa lý vật lý,Physical geography